Локализация и подавление горения лесных материалов с применением авиации: [монография] - Глушков Д. О. Дмитрий Олегович; Копылов Н. П. Николай Петрович; Кропотова С. С. Светлана Сергеевна; Кузнецов Г. В. Гений Владимирович; Стрижак П. А. Павел Александрович; Коробейничев О. П. (Новосибирск, Изд-во СО РАН, 2020)
Авт. указ. на обороте тит. л.